Alzheimer's disease biomarker‐guided diagnostic workflow using the added value of six combined cerebrospinal fluid candidates: Aβ1–42, total‐tau, phosphorylated‐tau, NFL, neurogranin, and YKL‐40. Issue 4 (9th January 2018) - Hampel, Harald; Toschi, Nicola; Baldacci, Filippo; Zetterberg, Henrik; Blennow, Kaj; Kilimann, Ingo; Teipel, Stefan J.; Cavedo, Enrica; Melo dos Santos, Antonio; Epelbaum, Stéphane; Lamari, Foudil; Genthon, Remy; et al.
Abstract: Introduction: The diagnostic and classificatory performances of all combinations of three core (amyloid β peptide [i.e., Aβ1–42 ], total tau [t‐tau], and phosphorylated tau) and three novel (neurofilament light chain protein, neurogranin, and YKL‐40) cerebrospinal fluid biomarkers of neurodegeneration were compared among individuals with mild cognitive impairment (n = 41), Alzheimer's disease dementia (ADD; n = 35), frontotemporal dementia (FTD; n = 9), and cognitively healthy controls (HC; n = 21), using 10‐fold cross‐validation. Methods: The combinations ranking in the top 10 according to diagnostic accuracy in differentiating between distinct diagnostic categories were identified. Results: The single biomarkers or biomarker combinations generating the best area under the receiver operating characteristics (AUROCs) were the following: the combination [amyloid β peptide + phosphorylated tau + neurofilament light chain] for distinguishing between ADD patients and HC (AUROC = 0.86), t‐tau for distinguishing between ADD and FTD patients (AUROC = 0.82), and t‐tau for distinguishing between FTD patients and HC (AUROC = 0.78). Conclusions: Novel and established cerebrospinal fluid markers perform with at least fair accuracy in the discrimination between ADD and FTD. The classification of mild cognitive impairment individuals was poor. Highlights: Interest in novel biomarkers of neurodegeneration is growing. We measured novel and established cerebrospinal fluid biomarkers. The diagnostic performances of all combinations were investigated. We identified the biomarker combinations with the highest accuracy. Longitudinal investigations are required to validate our data.